The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.14202/vetworld.2020.465-470
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of brucellosis in livestock in the wildlife and livestock interface area of Similipal Biosphere Reserve, India

Abstract: Background and Aim: Brucellosis is an important zoonotic disease that affects fertility in farm animals. The risk factors of brucellosis have not been well studied. This study aimed to understand the seroprevalence and risk factors of brucellosis among livestock in Bangriposi block of Mayurbhanj district in Odisha, a region that borders Similipal wildlife reserve. Materials and Methods: Rose Bengal plate test (RBPT) was carried out to estimate the seroprevalence of the livestock in this region. Bivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The presence of important zoonotic diseases, viz . listeriosis, brucellosis, tuberculosis, leptospirosis and scrub typhus, recorded in the present collaborative research was in accordance with Indian reports 1 8 9 10 11 12 13 14 15 16 17 18 19 20 21 . The study on vectors revealed novel findings, especially in scrub typhus and listeriosis.…”
Section: Discussionsupporting
confidence: 92%
“…The presence of important zoonotic diseases, viz . listeriosis, brucellosis, tuberculosis, leptospirosis and scrub typhus, recorded in the present collaborative research was in accordance with Indian reports 1 8 9 10 11 12 13 14 15 16 17 18 19 20 21 . The study on vectors revealed novel findings, especially in scrub typhus and listeriosis.…”
Section: Discussionsupporting
confidence: 92%
“…In Pakistan, the high age-wise prevalence was recorded as 32.25% (98/304) by enzyme-linked immunosorbent assay (ELISA) ( P < 0.05) in 21- to 30-year-old females ( 9 ). In India, the seroprevalence of brucellosis among cattle and goats was estimated to be 1.1 and 11.2%, respectively ( 10 ). Brucellosis is still reported from all types of farms and domestic livestock in Russia; between 1999 and 2009, the number of infected sites increased, ranging from 54 in 2001 to 112 in 2009 ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Brucellosis is a bacterial infection caused by a bacterium of the genus Brucella which is distributed worldwide and transmitted to humans from infected animals 1,2 . Brucellaabortus, Brucella suis, and Brucella melitensis are species that infect cattle, pigs, sheep, and goats and are responsible for most human cases 3,4,5 .…”
Section: Introductionmentioning
confidence: 99%